Analisis Pengaruh Capital Adequacy Ratio (Car), Non Performing Financing (Npf), Net Interest Margin (Nim), Financing To Deposit Ratio (Fdr), Biaya Operasional Terhadap Pendapatan Operasional (Bopo) Terhadap Profitabilitas Pada Bank Syariah Di Indonesia - Aziz, Habibul; , Zulfa Irawati., SE., MSi (2016)
This study aimed to analyze the positive and significant effect of the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Financing to Deposit Ratio (FDR) and Operating Expenses to Operating Income (ROA) partially on profitability (ROA) and the negative influence and significant Non Performing Financing (NPF) partially on profitability (ROA) on Islamic Banks in Indonesia 2012-2014. The population in this study using Islamic Banks in Indonesia 2012-2014. Samples of this study were 11 Islamic Banks with the sample method used was purposive sampling is a sampling method that takes an object with certain criteria. Data analysis method used is multiple linear regression analysis and hypothesis testing using t-statistics, F-statistics, and the coefficient of determination. From the analysis during the observation period t test results showed that the variables of the Capital Adequacy Ratio, Financing to Deposit Ratio and Operating Expenses to Operating Income partially no significant effect on profitability, while Non-performing Financing and Net Interest Margin significant effect on profitability. The results of the analysis of F test found that the variable Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), net interest margin (NIM), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (ROA) together influential significantly on profitability (ROA). The results of the analysis coefficient of determination (R 2) obtained Adjusted R Square (R 2) of 0.515, demonstrating that Profitability can be explained by the variable CAR, NPF, NIM, FDR, and ROA amounted to 51.5%, while the rest is explained 48 , 5% are influenced by other factors beyond the variables studied. The results of this study suggest Islamic Banks should improve the quality of earning assets / financing and some Islamic Banks BOPO reduce the ratio to below 97% so that the increase in net income.